Preparation, Antidermatophyte Activity, and Mechanism of Methylphloroglucinol Derivatives - Ye, Lianbao; Lin, Pengfei; Du, Wenjun; Wang, Yuanyuan; Tang, Chunping; Shen, Zhibin (Frontiers in Microbiology, 2018)
Our group isolated a variety of phlorglucinols from the plant and activity experiment showed that the phlorglucinols had strong antifungal activity, especially methylphlorglucinol derivatives such as aspidin PB, dryofragin, aspidinol, aspidin BB, aspidin AB, and albicanol, in which the hydroxyl group of methylphloroglucinol is the active group of compounds, and C-2 or C-6 is active site. The introduction of different groups in this position could change the properties and bioactivity of the compounds. In this study, different functional groups were introduced to the structure of methylphloroglucinol to obtain methylphlorglucinol derivatives, which were synthesized, evaluated anti-dermatophyte activities on Trichophyton rubrum, Trichophyton mentagrophytes, Microsporum canis and Gypsum microspore bacteria. Molecular docking verified their ability to combine protein binding site. Anti-dermatophyte mechanism of compounds on CYP51, squalene epoxidase and β-1,3-glucan synthase were investigated by ELISA. The results showed that compounds had inhibitory effect on 4 kinds of common dermatophytes in varying degrees, in which compound g was the strongest activities, the binding mode of methyl-phloroglucinol and its derivatives were similar to those of three enzymes, and compound e and compound g had significant effects on the activity of three enzymes, and compound g had a slightly stronger effect than the blank group. Compounds e and g had also significant effect of on ergosterol synthesis of Microsporum canis. This study could supply some anti-dermatophyte leading structure and possible mechanism for studying and developing new antifungal agents.